2017
DOI: 10.1007/s10620-017-4830-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Pharmacological Management of Gastroesophageal Reflux Disease

Abstract: The management of proton pump inhibitor-refractory GERD (rGERD) is a challenge in clinical practice. Since up to one-third of patients with typical GERD symptoms (heartburn and/or acid regurgitation) are not satisfied with proton pump inhibitor (PPI) therapy, new drug development targeting different pathophysiologies of GERD is imperative. At present, no other drugs serve as a more potent acid suppression agent than PPIs. As an add-on therapy, histamine type-2 receptor antagonists, alginates, prokinetics and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 186 publications
0
13
0
Order By: Relevance
“…Additionally, we have demonstrated that cashew gum decreases inflammation in the esophagus and reverses the decrease in epithelial resistance and increase in mucosal permeability that is associated with esophageal inflammation in experimental NERD models 22 . Consequently, we believe cashew gum is a promising agent for the treatment of LPR, that may work through a regurgitation‐associated mechanism similar to alginate 33 . In this mechanism, the topical agent associated with gastric refluxate reaches the upper airway tract and forms a temporary shield, which increases the laryngeal pre‐epithelial defense.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, we have demonstrated that cashew gum decreases inflammation in the esophagus and reverses the decrease in epithelial resistance and increase in mucosal permeability that is associated with esophageal inflammation in experimental NERD models 22 . Consequently, we believe cashew gum is a promising agent for the treatment of LPR, that may work through a regurgitation‐associated mechanism similar to alginate 33 . In this mechanism, the topical agent associated with gastric refluxate reaches the upper airway tract and forms a temporary shield, which increases the laryngeal pre‐epithelial defense.…”
Section: Discussionmentioning
confidence: 91%
“…22 Consequently, we believe cashew gum is a promising agent for the treatment of LPR, that may work through a regurgitation-associated mechanism similar to alginate. 33 In this mechanism, the topical agent associated with gastric refluxate reaches the upper airway tract and forms a temporary shield, which increases the laryngeal pre-epithelial defense.…”
Section: E893mentioning
confidence: 99%
“…To test the diffusion hypothesis, we conducted a series of studies with oesophageal preparations that were subjected to a suspension enriched with alginate, a topical oesophageal protectant that is currently used in clinical practice (Kung et al, 2017). Alginate appears to coat the luminal surface of the oesophagus, adhering to the mucosa as an additional barrier (Woodland et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms with the highest score were: heartburning, sensation of something sticking in the throat or a lump in the throat, and clearing throat, whereas breathing difficulties or choking episodes had the lowest score. The total score was 16 [14][15][16][17][18][19][20] in the EMERGE patients was significantly higher than in the RELIEFE patients: 16 [12][13][14][15][16][17][18][19][20] (p < 0.001; data not shown). Interestingly, RELIEF patients had significantly higher scores for some symptoms, including lump sensation, cough, dyspnea, hoarseness, and throat clearing, whereas EMERGE patients had higher scores for heartburn and difficult swallowing.…”
Section: Clinical Experiencementioning
confidence: 99%
“…Therefore, acid suppression is the mainstay of therapy for gastric reflux, and PPIs are the most effective drug in this approach [18,19]. Although PPIs are the treatment of choice for GERD, still approximately one-third of patients with GERD fail to respond symptomatically to a standard dose PPI, either partially or completely [20].…”
Section: Introductionmentioning
confidence: 99%